One-Dimensional High-Resolution Wavefront Sensor Enabled by Subwavelength Compound Gratings - Yunlong Meng; Xinyu Shen; Junyang Xie; Yao Peng; Xiaowen Shao; Feng Yan; Cheng Yang (Photonics, 2023)
Angle sensors are widely used for wavefront measurements, which is attributed to their integration and robustness. Currently, commercial sensors are available with pixel sizes in the order of wavelengths. However, the spatial resolution of angle sensors still lags far behind. Here, we report a one-dimensional, high-resolution wavefront sensor. It was produced by introducing subwavelength compound gratings above the pixels. The gratings involved could be replaced by the sensor’s intrinsic readout circuitry without additional operation. The experimental results showed that it had a spatial resolution of 1.4 µm, two orders of magnitude higher than that of the Shack–Hartmann wavefront sensor. The significant increase in spatial resolution enables angle sensors to reconstruct complex wavefronts accurately.